(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to determine the effects of adjuvant therapy on body mass index (BMI) and body fat (BF) measurements in women with early-stage breast cancer (ESBC).Material and Methods: We prospectively evaluated BMI and BF measurements including trunk fat mass kilograms (kg), trunk fat mass (%) and total body fat (%) on a bioelectric impedance analyzer in 29 women with stages I-III breast cancer. All of the patients received anthracycline-based adjuvant chemotherapy (ACT). Six patients were hormone receptor (HR)-negative. Twenty-three patients were HR-positive and received adjuvant endocrine therapy (AET) following ACT. Eleven HR-positive postmenopausal patients were treated with an aromatase inhibitor (AI), and the remaining twelve HR-positive premenopausal patients were treated with tamoxifen (TMX). A total of 3 measurements were performed in the beginning of chemotherapy, at 6th, and 12th months.Results: Although the BMI was significantly increased, there was no significant change in the BF during chemotherapy in patients receiving only ACT. Both BMI and BF measurements were significantly increased in premenopausal patients receiving TMX after ACT. However, no significant change was observed in BMI and BF measurements in postmenopausal patients receiving AI after ACT.Conclusions: ACT increased both BMI and BF measurements in patients with HR-positive premenopausal ESBC. Treatment with TMX or AI after ACT did not enhance the changes due to chemotherapy on body composition. Therefore, especially patients with HR-positive premenopausal ESBC should be careful not to gain weight during ACT.Keywords: Early breast cancer; adjuvant therapy; body mass index; body fat measurements.